Rancang Bangun Mesin Pengerolan Pipa 1,5 Inci Menggunakan Motor Listrik Sebagai Penggerak dan Dongkrak 2 Ton Sebagai Penekan Pipa - Sirama Sirama; Simon Parekke (Infotekmesin, 2021)
The 1.5 inch pipe rolling machine utilizes an electric motor to drive the pipe holder and a 2ton jack as a pipe press. Although the roller machine is widely used in conventional workshops by using human power, it causes the pipe rolling time to be long and the machine user gets tired quickly. This is due to lack of resources to think about developing and improving the performance of these machines. Therefore, the focus of this research is the design of a 1.5 inch pipe rolling machine using an electric motor as a drive and a 2 ton jack as a pipe press. This research aims to produce a design and machine for 1.5 inch pipe rolling and to help accelerate the pipe rolling process and reduce worker fatigue. This pipe rolling machine consists of several components, namely, the engine frame, electric motor, gearbox reducer, chain-sprocket, shaft, pipe drive wheel, hydraulic pump and so on. The working process of this machine begins by preparing a 1.5 inch x 3 meter pipe then the pipe is positioned above the drive wheel, lowers the upper pressure wheel to the desired depth with a 2ton jack power, turn on the electric motor and press the button to roll the pipe back and forth and so on. up to pipe roll size as needed. The stages in making this machine are design, detailed drawing, manufacturing process, quality control, assembly and testing, data retrieval and data analysis. The research resulted in drawings of the design and manufacture of the machine, the calculation of the rotational speed of the machine for optimal rolling obtained 20.46 rpm and an average pipe rolling time of 6.80 minutes for one workpiece. This machine can still be optimized by adding a workpiece movement limiter when rolling.